Genetic dissection and mapping of novel quantitative trait loci (QTLs) associated with powdery mildew resistance in chilli (Capsicum annuum L.) - Rohit Kumar; B.V. Tembhurne; V. Hanumanth Nayak; B. Kisan; K.M. Shivaprasad; J.M. Nidagundi; G.Y. Lokesh; Y.S. Amaresh (Physiological and Molecular Plant Pathology, 2026)

Status of insecticide resistance and detoxification enzymes activity in pink bollworm, Pectinophora gossypiella (Saunders) populations from India - K. Srilekha; A. G. Sreenivas; Jaba Jagdish; Pramod Katti; S. G. Hanchinal; Y. S. Amaresh; M. Lakshmikanth; Sujit Kumbhare; Pooja Verma; Vivek Shah; G. T. Behere; Y. G. Prasad; et al. (Ecotoxicology, 2026)

Application of time-domain electromagnetic data in 3D mapping of buried paleochannels hosting sandstone type uranium mineralization in Satpura Gonwana basin, India - M. Sridhar; A.K. Maurya; Amaresh Kumar; Rakesh Mohan; Srinjoy Mukharjee; S.K. Dash; R. Mamallan (Journal of Applied Geophysics, 2026)

Accelerating genetic gain through integrated genomic selection in crop plants - Bandela Edukondalu; Nunavath Aswini; Amaresh; Gopalareddy Krishnappa; Buruka Soundharya; Gottimukkala Nikhitha; T. Lakshmi Pathy; Kasanaboina Krishna; Yadla Hari; Vinayaka (Journal of Applied Genetics, 2026)

Strategic considerations for nutrient use efficiency in sugarcane: Physiological, molecular and genetic perspectives - V. Krishnapriya; R. Manimekalai; R. Gomathi; Van Hay Duong; R. Arunkumar; P.T. Prathima; K. Devakumar; K. Thamilarasi; H.K. Mahadeva Swamy; Amaresh; P. Govindaraj; Prasanta K. Dash (Plant Science, 2026)

Mapping agricultural vulnerability to climate-driven drought using the TOPSIS model - Kiran Kumar Mohapatra; Amaresh Kumar Nayak; Ranjan Kumar Patra; Rahul Tripathi; Chinmaya Kumar Swain; Rasu Eeswaran; Saheed Garnaik (Theoretical and Applied Climatology, 2026)

Deciphering low nitrogen tolerance of wheat in mega-environments using integrated multivariate approaches - Gopalareddy Krishnappa; Hanif Khan; Amaresh; Vinayaka; T. Lakshmi Pathy; Arun Gupta; Anju Mahendru-Singh; Arvind Kumar Ahlawat; Jasavantlal Manilal Patel; Suma S. Biradar; Harohalli Masthigowda Mamrutha; Rinki Khobra; et al. (European Journal of Agronomy, 2026)

Deciphering True Seed Viability Loss in Sugarcane: Physiological and Ultrastructural Evidence of Embryo Dehydration as a Marker of Seed Recalcitrance - V. G. Dhanya; V. V. Prathiba; Amaresh; Savio Jacob Saji; M. Neethu; E. K. Saneera; M. Nisha (Sugar Tech, 2026)

A data driven assessment to link tropospheric methane concentration and surface biophysical factors using remotely sensed data - Sudipta Manna; Argha Ghosh; Akhilesh Kumar Gupta; Arnab Mandal; Araya Kumar Biswamohan Mohapatra; Amaresh Khuntia (Remote Sensing Applications: Society and Environment, 2026)

An integrated Fermatean fuzzy MCDM approach for optimal medical waste treatment technology selection - Madhumita Behera; Amaresh Chandra Panda (Process Safety and Environmental Protection, 2026)

Development of multifunctional structures for spacecraft applications - K.K. Sairajan; Lopamudra Mishra; Amaresh Virupakshi Channi; S. Rajesha Kumar; M. Kotresh; D. Shanthi (Advances in Space Research, 2026)

Genomic Exploration for the Sucrose Content in Sugarcane - N. Aswini; J. Moniusha; S. Keerthana; Amaresh; M. Nandhini; P. T. Prathima; K. Mohanraj; Shweta Kumari; R. Manimekalai (Tropical Plant Biology, 2025)

Transcription Factors in Plant Biotic and Abiotic Stress Responses: Potentials and Prospects in Sugarcane - Aswini Nunavath; Amaresh; Nandhini Murugan; S. Keerthana; Shweta Kumari; B. Singaravelu; A. Ramesh Sundar; R. Manimekalai (Tropical Plant Biology, 2025)

Disclosure of Productive and Stable Sugarcane Genotypes for Cane Yield and Quality Traits Using Various Stability Statistics - Ravinder Kumar; Mintu Ram Meena; Pooja Dhansu; Manohar Lal Chhabra; Chinnaswamy Appunu; V. Sreenivasa; A. Anna Durai; H. K. Mahadeva Swamy; Amaresh (Tropical Plant Biology, 2025)

Elucidating the G X E Interaction Using AMMI, AMMI Stability Parameters and GGE for Cane Yield and Quality in Sugarcane - A. Anna Durai; Amaresh; R. Arun Kumar; G. Hemaprabha (Tropical Plant Biology, 2025)

Multi-trait index based Elucidation of drought tolerance potential of Saccharum spontaneum - T. Lakshmi Pathy; V. Vinu; R. Arunkumar; Gopalareddy Krishnappa; H. K. Mahadeva Swamy; R. Valarmathi; K. Dhanapal; Amaresh; P. Govindaraj; G. Hemaprabha; Bakshi Ram (Plant Physiology Reports, 2025)

Review of Nano-clay Polymer Composites for Controlled Nitrogen Release: Prospects and Limitations - Bitish Kumar Nayak; Dibyendu Chatterjee; Ranjan Paul; Saikat Ranjan Das; Totan Adak; Nintu Mandal; Julia Drewer; Abhijit Pradhan; Manik Chandra Kundu; Asit Kumar Pal; Gour Hari Santra; Suryakanta Sahoo; et al. (Agricultural Research, 2025)
This review paper discusses the potential and limitations of polymer composites for smart nitrogen (N) supply to meet the needs of agricultural crops. Unlike most conventional fertilizers, nano-clay polymer composites (NCPCs) offer a slow-release mechanism that enhances nitrogen use efficiency and reduces its loss to the environment. NCPCs are normally synthesized using solution blending, melt blending and in situ polymerization. Solution blending offers a better clay dispersion in the polymer matrix than melt blending owing to its low viscosity and strong stirring force. NCPCs have been characterized by several techniques, including equilibrium water absorbency, Fourier transform infrared spectroscopy, scanning electron microscopy, X-ray diffraction and nutrient release kinetics. The potential benefits of using these composites are highlighted, including improved nitrogen use efficiency and reduced environmental impacts, as are their prospects for widespread use in agriculture and mitigation of the adverse environmental effects from conventional fertilizers. In addition, the limitations of NCPC technology, such as cost, scalability and potential negative environmental effects, are also investigated. The paper provides a wide perspective on the NCPC technology, including the regulatory environment and policy, industry trends and commercialization potential. NCPCs offer many benefits to increase nitrogen use efficiency and reduce pollution affecting water quality, air quality and climate. The main current barrier to overcome is to reduce production costs, so that farmers may also benefit financially from the higher nitrogen use efficiency and associated reduced amounts of nitrogen wasted to the environment.

Evaluation of micronutrient retention and bioavailability in diverse rice genotypes: Role of phytate to iron and zinc molar ratio - Swetaleen Mohapatra; Lopamudra Nayak; Monalisha Biswal; Umakanta Ngangkham; Nihar Ranjan Singh; C. Parameswaran; Sangita Mohanty; Awadhesh Kumar; Amaresh Kumar Nayak (Journal of Cereal Science, 2025)

Harnessing Fly Ash for Water Purification: Advances in Sustainable Waste Management and Environmental Protection - Vivek Saxena; Saibal Manna; Saurabh Kumar Rajput; Amaresh Gantayet (Water, Air, & Soil Pollution, 2025)

Correction to: Rapid urbanization leads to decline in forest cover and ecosystem services in India: insights from 10-m ESA Sentinel-2 land use land cover product - Sumanta Chatterjee; Smruthi Sagarika Mahapatra; Amaresh Kumar Nayak; Vikas Kumar Rai; Prakash Jha; Seyed Roohollah Mousavi (Theoretical and Applied Climatology, 2025)

Next-generation molecular breeding tools to harness higher genetic gains in sugarcane - Amaresh; Nunavath Aswini; Gopalareddy Krishnappa; A. Anna Durai; R. Manimekalai; H. K. Mahadeva Swamy; T. Lakshmi Pathy; Vinayaka; V. G. Dhanya; N. D. Rathan; S. Nandakumar; K. Shwetha; et al. (Planta, 2025)

Rapid urbanization leads to decline in forest cover and ecosystem services in India: insights from 10-m ESA Sentinel-2 land use land cover product - Sumanta Chatterjee; Smruthi Sagarika Mahapatra; Amaresh Kumar Nayak; Vikas Kumar Rai; Prakash Jha; Seyed Roohollah Mousavi (Theoretical and Applied Climatology, 2025)
This research investigates short-term land use and land cover (LULC) changes and their impact on ecosystem services in eastern India from 2017 to 2022. It highlights how LULC alterations affect hydrodynamic variables and social factors. Using a globally established database, Ecosystem Service Values (ESV) were assessed through LULC analysis. The findings reveal a concerning decline in rainfall and vegetation health over the study period, suggesting potential climate change impacts. Notably, rainfall deviations in 2017 and 2022 were greater than the 30-year long-term average. Analysis using 10-m ESA Sentinel-2 remote sensing data indicated a 39.14% urban area expansion, while forest cover decreased by 9.76%, leading to an estimated loss of US$1,216 million in ESV. Conversely, ESV from croplands increased slightly by US$0.35 million, indicating possible improvements in irrigation infrastructure in Odisha. Wetland ESV also rose by 2.14% (US$8.81 million). The study highlights the critical role of LULC changes in influencing hydrodynamic variables such as rainfall and soil moisture, as well as social factors like urbanization. Understanding these interconnections is essential for effective land use planning and management. The findings can inform future policies, particularly in ecosystem service payments and rural livelihood improvements, ensuring sustainable development in the region. Graphical Abstract

Deciphering Drought Tolerance Potential of Saccharum spontaneum in Tropical Climates Using Multivariate Techniques - V. Vinu; T. Lakshmi Pathy; H. K. Mahadeva Swamy; Gopalareddy Krishnappa; R. Arun Kumar; R. Valarmathi; R. Gobu; V. Sreenivasa; R. T. Maruthi; Amaresh; P. Govindaraj (Sugar Tech, 2025)

Soil carbon and nitrogen dynamics under conservation agriculture components for direct seeded rice-green gram system - Gayatri Patra; Dibyendu Chatterjee; Khitish Chandra Moharana; Bitish Kumar Nayak; Rahul Tripathi; Mohammad Shahid; Dipti Ranjan Pani; Saikat Ranjan Das; Bipin Bihari Panda; Sushmita Munda; Upendra Kumar; Abhijit Pradhan; et al. (Plant and Soil, 2025)

Novel designs and performance appraisal of non-uniformly heated annuli for heat transfer augmentation with supercritical carbon dioxide - Ashok Kumar Gond; Amaresh Dalal; Dipankar N. Basu (Annals of Nuclear Energy, 2025)

Genome-Wide Expression Profiling of Cytochrome P450 Genes in Response to the Oxidative Stress in Saccharum spp. - Aswini Nunavath; Amaresh; M. Nandhini; S. Keerthana; Rajeev Kumar; R. S. Gujjar; R. Gomathi; A. Selvi; P. Govindaraj; R. Manimekalai (Sugar Tech, 2025)

Suppressing Mycobacterium tuberculosis virulence and drug resistance by targeting Eis protein through computational drug discovery - Geethu S. Kumar; Amaresh Kumar Sahoo; Nishant Ranjan; Vivek Dhar Dwivedi; Sharad Agrawal (Molecular Diversity, 2025)

Diagnostic and therapeutic strategies in combating implanted medical device-associated bacterial biofilm infections - Ayush Amod; Ananya Anurag Anand; Amaresh Kumar Sahoo; Sintu Kumar Samanta (Folia Microbiologica, 2025)

Impact of Biochar and Water Regimes on Arsenic Transfer and Uptake in Rice: Insights into Transporter Behaviour and Soil–Plant Dynamics - Rubina Khanam; Lipsa Tripathy; Parameswaran Chidambaranathan; Pedda Ghouse Peera Sheikh Kulsum; Jajati Mandal; Mohammad Shahid; Manish Debnath; Raj Kishore Sahoo; Sushmita Munda; Sanghamitra Samantray; Amaresh Kumar Nayak (Exposure and Health, 2025)

Quantifying Climate Influence on Net Ecosystem Exchange in Lowland Tropical Rice: A Five-Year Eddy Covariance Study - Chinmaya Kumar Swain; Amaresh Kumar Nayak; Dibyendu Chatterjee; Suchismita Pattanaik; Vijayakumar Shanmugam; Sumanta Chatterjee; Pratap Bhattacharyya; Rahul Tripathi; Mohammad Shahid; Kiran Kumar Mohapatra; Abhijit Pradhan; Nihar Ranjan Singh (Agricultural Research, 2025)

Evaluation of Saccharum and Erianthus Introgressed Early Generation Novel Sugarcane Hybrids as Potential Sources of Biomass for Cogeneration - Sreenivasa Venkatarayappa; Mahadevaiah Channappa; Amaresh; Ravinder Kumar; Arun Kumar Raja; Mintu Ram Meena; Anna Durai Ayyadurai; Appunu Chinnaswamy; Hemaprabha Govindakurup; Govindaraj Perumal (Sugar Tech, 2025)

Advanced Genome Editing Technologies: Potentials and Prospects in Improvement of Sugar crops - G. Amaresh; Aswini Nunavath; C. Appunu; C. Viswanathan; Rajeev Kumar; R. S. Gujjar; R. Manimekalai (Sugar Tech, 2025)

Unraveling the Stability of Sugarcane Clones Using Multivariate Stability Models for Cane Yield and Quality Under Subtropical Climates - Mintu Ram Meena; Ravinder Kumar; R. Karuppaiyan; Neeraj Kulshreshtha; Manohar Lal Chhabra; Amaresh; Gopalareddy Krishnappa; Aswini Nunavath; K. Mohanraj; Perumal Govindaraj; Govind Hemaprabha (Sugar Tech, 2024)

High throughput phenotyping using hyperspectral imaging for seed quality assurance coupled with machine learning methods: principles and way forward - V. G. Dhanya; A. Subeesh; C. Susmita; Amaresh; Savio Jacob Saji; C. Dilsha; C. Keerthi; Aswini Nunavath; A. N. Singh; Sanjay Kumar (Plant Physiology Reports, 2024)

Symbiotic orchestra: Tripartite ecology building by scalable microfluidics nano-fibre for sustainable cultivation - Bandana Kumari Sahu; Kamaljit Kaur; Debasis Mitra; Vibhav Katoch; Prem Kumar; Navjot Singh; Deepa Singh; Rita Choudhary; Amaresh Kumar Nayak; Bhanu Prakash; Periyasamy Panneerselvam; VijayaKumar Shanmugam (Chemical Engineering Journal, 2024)

Exploring the Potential of Designed Peptides Containing Lysine and Arginine Repeats against VIM-2 Metallo-Beta-Lactamases - Ananya Anurag Anand; Amaresh Kumar Sahoo; Sintu Kumar Samanta (International Journal of Peptide Research and Therapeutics, 2024)

Silica and polymer coated controlled release nitrogen-phosphorus fertilizer for improving nutrient and water use efficiency in semi-arid India - Avijit Ghosh; Amit K. Singh; R.V. Kumar; Prashant D. Singh; Sukanya Misra; Safik Ahamed; Deepak Ojha; Amaresh Chandra; Ranjan Bhattacharyya (Journal of Environmental Chemical Engineering, 2024)

3D printing of rice starch incorporated peanut protein isolate paste: Rheological characterization and simulation of flow properties - Amaresh Kadival; Jayeeta Mitra; Rajendra Machavaram; Manish Kaushal (Innovative Food Science & Emerging Technologies, 2024)

Enhancing soil quality and yield through microbial assisted in-situ residue management in rice-rice cropping system in Odisha, Eastern India - Periyasamy Panneerselvam; Ansuman Senapati; Debasis Mitra; Ankita Priyadarshini; Smriti Shadangi; Suchismita Behera; Upendra Kumar; Anjani Kumar; Mohammad Shahid; Sandeep Sharma; Rajendra Singh Garhwal; Indra Mani; et al. (Journal of Environmental Management, 2024)

Ecological dynamics of Arbuscular Mycorrhizal Fungi in wetland and aerobic rice ecosystem under subtropical humid climatic conditions in Eastern India - Ansuman Senapati; Periyasamy Panneerselvam; Parameswaran Chidambaranathan; Amaresh Kumar Nayak; Debasis Mitra; Chinmay Pradhan; Annamalai Anandan (Symbiosis, 2024)

Reducing the environmental impact of rice production in subtropical India by minimising reactive nitrogen loss - Dibyendu Chatterjee; Saikat Ranjan Das; Sangita Mohanty; Baishnab Charan Muduli; Arti Bhatia; Bitish Kumar Nayak; Robert M. Rees; Julia Drewer; Amaresh Kumar Nayak; Tapan Kumar Adhya; Chidambaranathan Parameswaran; Jitendriya Meher; et al. (Journal of Environmental Management, 2024)

Bacillus subtilis strain BS87 as a biocontrol agent against spot blotch disease: effect on growth, nutrient status, and antioxidant enzymes in wheat - Priyanka Chandra; Rinki Khobra; Parul Sundha; Amaresh Chandra; Rakesh Kumar Sharma; Gyanendra Pratap Singh (Acta Physiologiae Plantarum, 2024)

Strength, life cycle analysis, embodied energy and cost-sensitivity assessment of sugarcane bagasse ash-based ternary blends of geopolymer concrete - Amaresh Tripathy; Prasanna Kumar Acharya (European Journal of Environmental and Civil Engineering, 2024)

Climate-smart deficit irrigation and nutrient management strategies to conserve energy, greenhouse gas emissions, and the profitability of fodder maize seed production - Hanamant M. Halli; Prabhu Govindasamy; V.K. Wasnik; B.G. Shivakumar; Sunil Swami; Mukesh Choudhary; V.K. Yadav; A.K. Singh; N. Raghavendra; Venkadasamy Govindasamy; Amaresh Chandra; K. Sammi Reddy (Journal of Cleaner Production, 2024)

Life cycle greenhouse gas emissions from five contrasting rice production systems in the tropics - Pradeep K. DASH; Pratap BHATTACHARYYA; Soumya R. PADHY; Amaresh K. NAYAK; Annie POONAM; Sangita MOHANTY (Pedosphere, 2023)

Phenotypic characterization of the novel seedling stage zebra leaf mutant, Pusa Zebra 18 in rice - Amaresh; Gopala Krishnan Subbaiyan; Kunnummal Kurungara Vinod; Viswanathan Chinnusamy; Amitha Charu Rama Mithra Viyasamurt Sevanthi; Raju Dhandapani; Ranjith Kumar Ellur; Prolay Kumar Bhowmick; Haritha Bollinedi; Palaniyandi Umadevi; Manoranjan Senapati; Rakesh Kumar Verma; et al. (Plant Physiology Reports, 2023)

Targeting notch signaling pathway in breast cancer stem cells through drug repurposing approach - Yamini Pathak; Ihosvany Camps; Amaresh Mishra; Vishwas Tripathi (Molecular Diversity, 2023)

Co-applied Nitrogen and Auxin via Nano-clay-Polymer Composites Enhances Yield and Nitrogen Use Efficiency - Dibyendu Chatterjee; Totan Adak; Bitish Kumar Nayak; Ranjan Paul; Abhijit Pradhan; Mark A. Sutton; Julia Drewer; Saikat Ranjan Das; Amaresh Kumar Nayak; Himanshu Pathak (Journal of Soil Science and Plant Nutrition, 2023)

Rhizospheric Trichoderma harzianum TBR-7 in combination with chitosan for eco-friendly management of crown rot disease in Egyptian clover (Trifolium alexandrinum L.) - Nitish Rattan Bhardwaj; Maneet Rana; Pushpendra Koli; Rahul Kaldate; Ajoy Kumar Roy; Amaresh Chandra (European Journal of Plant Pathology, 2023)

Silica sources for arsenic mitigation in rice: machine learning-based predictive modeling and risk assessment - Rubina Khanam; Amaresh Kumar Nayak; Pedda Ghouse Peera Sheikh Kulsum; Jajati Mandal; Mohammad Shahid; Rahul Tripathy; Pratap Bhattacharyya; Panneer Selvam; Sushmita Munda; Sivashankari Manickam; Manish Debnath; Raghavendra Goud Bandaru (Environmental Science and Pollution Research, 2023)

Dual metal ion (Fe3+ and As3+) sensing and cell bioimaging using fluorescent carbon quantum dots synthesised from Cynodon dactylon - Sweta Gurung; Neha; Nimmala Arun; Mayank Joshi; Tanya Jaiswal; Anand P. Pathak; Parimal Das; Amaresh Kumar Singh; Ajay Tripathi; Archana Tiwari (Chemosphere, 2023)

Marine estuaries act as better sink for greenhouse gases during winter in undisturbed mangrove than degraded ones in Sundarban, India - Pratap Bhattacharyya; Soumya Ranjan Padhy; Rubina Khanam; Amaresh Kumar Nayak; Pradeep Kumar Dash; C.S. Reddy; Abhishek Chakraborty; Debashis Mandal; Saubhagyalaxmi Swain; M.J. Baig (Marine Environmental Research, 2023)

Long-term country-level evidence of major but uneven ruptures in the landscape of industrial modernity - Laur Kanger; Peeter Tinits; Anna-Kati Pahker; Kati Orru; Aro Velmet; Silver Sillak; Artjoms Šeļa; Olaf Mertelsmann; Erki Tammiksaar; Kristiina Vaik; Caetano C.R. Penna; Amaresh Kumar Tiwari; et al. (Environmental Innovation and Societal Transitions, 2023)

Potential soil organic carbon sequestration vis-a-vis methane emission in lowland rice agroecosystem - Saikat Ranjan Das; Bitish Kumar Nayak; Souvik Dey; Suman Sarkar; Dibyendu Chatterjee; Saurav Saha; Dibyendu Sarkar; Abhijit Pradhan; Sanjoy Saha; Amaresh Kumar Nayak (Environmental Monitoring and Assessment, 2023)

Carbon and water footprints of major crop production in India - Amaresh Kumar NAYAK; Rahul TRIPATHI; Manish DEBNATH; Chinmaya Kumar SWAIN; Biswaranjan DHAL; Shanmugam VIJAYKUMAR; Anshuman Debasis NAYAK; Sangita MOHANTY; Mohammad SHAHID; Anjani KUMAR; Manoj RAJAK; Khitish Chandra MOHARANA; et al. (Pedosphere, 2023)

Long-term impact of pulses crop rotation on soil fungal diversity in aerobic and wetland rice cultivation - Periyasamy Panneerselvam; Ansuman Senapati; Parameswaran Chidambaranathan; S.R. Prabhukarthikeyan; Debasis Mitra; Guru Prasanna Pandi Govindharaj; Amaresh Kumar Nayak; Annamalai Anandan (Fungal Biology, 2023)

The role of women’s empowerment on child nutrition in India: a longitudinal analysis - Poulami Chatterjee; Amaresh Dubey (Environment, Development and Sustainability, 2023)

Fluoride risk assessment from agricultural soils in India: a study based on vertical, spatial and geochemical distribution - Sunil Kumar Jha; Yogesh Kumar Sharma; Amaresh Kumar Nayak; Deepak; Devanand (Environmental Monitoring and Assessment, 2023)

A comprehensive overview on Micro RNA signature in type 2 diabetes Mellitus and its complications - Sanjukta Mishra; Jyotirmayee Bahinipati; RajLaxmi Sarangi; Soumya Ranjan Mohapatra; Swarnalata Das; Amaresh Mishra (Indian Journal of Clinical Biochemistry, 2023)

Influence of incorporation of peanut protein isolate on pasting, rheological and textural properties of rice starch - Amaresh Kadival; Jayeeta Mitra; Manish Kaushal (Journal of Food Engineering, 2023)

A state-of-the-art review on cadmium uptake, toxicity, and tolerance in rice: From physiological response to remediation process - Pedda Ghouse Peera Sheikh Kulsum; Rubina Khanam; Shreya Das; Amaresh Kumar Nayak; Filip M.G. Tack; Erik Meers; Meththika Vithanage; Mohammad Shahid; Anjani Kumar; Sukalyan Chakraborty; Tanushree Bhattacharya; Jayanta Kumar Biswas (Environmental Research, 2023)

Rice straw recycling: A sustainable approach for ensuring environmental quality and economic security - Anjani KUMAR; Amaresh Kumar NAYAK; Sandeep SHARMA; Ansuman SENAPATI; Debasis MITRA; Bipasa MOHANTY; Seenichamy Rathinam PRABHUKARTHIKEYAN; Kuttalingam Gopalasubramanian SABARINATHAN; Indra MANI; Rajendra Singh GARHWAL; Sugitha THANKAPPAN; Mahapatra Smruthi SAGARIKA; et al. (Pedosphere, 2023)

Paddy rice methane emissions across Monsoon Asia - Zutao Ouyang; Robert B. Jackson; Gavin McNicol; Etienne Fluet-Chouinard; Benjamin R.K. Runkle; Dario Papale; Sara H. Knox; Sarah Cooley; Kyle B. Delwiche; Sarah Feron; Jeremy Andrew Irvin; Avni Malhotra; et al. (Remote Sensing of Environment, 2023)

Amyloids on Membrane Interfaces: Implications for Neurodegeneration - Amaresh Kumar Mahakud; Jafarulla Shaikh; V. V. Rifa Iqbal; Abhinav Gupta; Anuj Tiwari; Mohammed Saleem (The Journal of Membrane Biology, 2022)

Land surface temperature distribution in Mahanadi delta: impact of land use land cover change - Rahul Tripathi; Khitish Chandra Moharana; Dibyendu Chatterjee; Manish Debnath; Sangita Mohanty; Anjani Kumar; Shanmugam Vijayakumar; Bhabani Shankar Satapathy; Bandaru Raghavendra Goud; Amaresh Kumar Nayak (Arabian Journal of Geosciences, 2022)

Sole- or Dual-Crop Basis Residue Mulching and Zn Fertilization Lead to Improved Productivity, Rhizo-modulation and Soil Health in Zero-Tilled Pigeonpea–Wheat Cropping System - Adarsh Kumar; K. S. Rana; Anil K. Choudhary; R. S. Bana; V. K. Sharma; Gaurendra Gupta; Sudhir K. Rajpoot; Ingudam Bhupenchandra; Mukesh Choudhary; Praveen Jakhar; Amit Kumar; Abhishek Kumar; et al. (Journal of Soil Science and Plant Nutrition, 2022)

Impact of Land Use and Land Cover Change on Ecosystem Services in Eastern Coast of India - Rahul Tripathi; Khitish Chandra Moharana; Sangita Mohanty; Suchismita Pattnaik; Dibyendu Chatterjee; Chinmaya Kumar Swain; Anjani Kumar; Prafulla Kumar Nayak; Bipin Bihari Panda; Debarti Bhaduri; Sushmita Munda; Rubina Khanam; et al. (International Journal of Environmental Research, 2022)

Evaluation of classical ayurvedic medicine “Sukumaram Kasayam” in a rat model of letrozole induced polycystic ovaries - Sujit Dash; Sunil Kumar Kanungo; Bishwanath Mishra; Amaresh Chandra Sahoo; Aswini Kumar Senapati; Sangyarani Pattnaik (Advances in Traditional Medicine, 2021)

Plant growth promoting Bacillus-based bio formulations improve wheat rhizosphere biological activity, nutrient uptake and growth of the plant - Priyanka Chandra; Rinki Khobra; Parul Sundha; Rakesh Kumar Sharma; Poonam Jasrotia; Amaresh Chandra; Devendra Pal Singh; Gyanendra Pratap Singh (Acta Physiologiae Plantarum, 2021)

Actual evapotranspiration and crop coefficients for tropical lowland rice (Oryza sativa L.) in eastern India - Sumanta Chatterjee; Paul C. Stoy; Manish Debnath; Amaresh Kumar Nayak; Chinmaya Kumar Swain; Rahul Tripathi; Dibyendu Chatterjee; Smruthi Sagarika Mahapatra; Ammara Talib; Himanshu Pathak (Theoretical and Applied Climatology, 2021)

DREBs-potential transcription factors involve in combating abiotic stress tolerance in plants - Kamini Singh; Amaresh Chandra (Biologia, 2021)

An updated review on the role of the CXCL8-CXCR1/2 axis in the progression and metastasis of breast cancer - Amaresh Mishra; Kamrul Hassan Suman; Nisha Nair; Jaseela Majeed; Vishwas Tripathi (Molecular Biology Reports, 2021)

Early Accumulation of Sucrose and Expression Behavior of Genes Associated with Sucrose Accumulation in Sugarcane Ratoon Crop Exposed to Gibberellin Influencing Source–sink Dynamics - Shruti Singh; Amaresh Chandra (Sugar Tech, 2021)

Partitioning of eddy covariance-measured net ecosystem exchange of CO2 in tropical lowland paddy - Sumanta Chatterjee; Chinmaya Kumar Swain; Amaresh Kumar Nayak; Dibyendu Chatterjee; Pratap Bhattacharyya; Smruthi Sagarika Mahapatra; Manish Debnath; Rahul Tripathi; Prabhat Kumar Guru; Biswaranjan Dhal (Paddy and Water Environment, 2020)

A Review on Basic Biology of Bacterial Biofilm Infections and Their Treatments by Nanotechnology-Based Approaches - Debjani Banerjee; P. M. Shivapriya; Pavan Kumar Gautam; Krishna Misra; Amaresh Kumar Sahoo; Sintu Kumar Samanta (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Health risks from trace elements in muscles of some commonly available fish in Australia and India - Mohammad Mahmudur Rahman; Muhammad Tahir Shehzad; Amaresh Kumar Nayak; Shruti Sharma; Marjana Yeasmin; Srikanta Samanta; Ray Correll; Ravi Naidu (Environmental Science and Pollution Research, 2020)

Determination of Morphological and Biochemical Basis of Resistance Against Top Borer, Scirpophaga excerptalis Walker in Sugarcane - S. N. Sushil; Amaresh Chandra; Sharmila Roy; A. K. Jaiswal; M. R. Singh; A. D. Pathak (Sugar Tech, 2020)

Potential Role of Appropriate Technological Interventions in Enhancing Income of Sugarcane Farmers in Subtropical India - M. M. Roy; Amaresh Chandra (Agricultural Research, 2019)

Water vapor flux in tropical lowland rice - Dibyendu Chatterjee; Amaresh Kumar Nayak; S. Vijayakumar; Manish Debnath; Sumanta Chatterjee; Chinmaya Kumar Swain; Priyanka Bihari; S. Mohanty; Rahul Tripathi; Mohammad Shahid; Anjani Kumar; H. Pathak (Environmental Monitoring and Assessment, 2019)

Promoting biofuels: the case of ethanol blending initiative in India - M. M. Roy; Amaresh Chandra (Clean Technologies and Environmental Policy, 2019)

Real-time monitoring of water requirement in protected farms by using polynomial neural networks and image processing - Amaresh Sarkar; Mrinmoy Majumder (Environment, Development and Sustainability, 2019)

Economic of a six-story stacked protected farm structure - Amaresh Sarkar; Mrinmoy Majumder (Environment, Development and Sustainability, 2019)

Cyanobiont diversity in six Azolla spp. and relation to Azolla-nutrient profiling - Upendra Kumar; Amaresh K. Nayak; Periasamy Panneerselvam; Anjani Kumar; Sangita Mohanty; Mohammad Shahid; Archana Sahoo; Megha Kaviraj; Himani Priya; Nitiprasad N. Jambhulkar; Pradeep K. Dash; S. D. Mohapatra; et al. (Planta, 2019)

Characterization of land surface energy fluxes in a tropical lowland rice paddy - Dibyendu Chatterjee; Rahul Tripathi; Sumanta Chatterjee; Manish Debnath; Mohammad Shahid; Pratap Bhattacharyya; Chinmaya Kumar Swain; Rojalin Tripathy; Bimal K. Bhattacharya; Amaresh Kumar Nayak (Theoretical and Applied Climatology, 2019)

Novel screening protocol for precise phenotyping of salt-tolerance at reproductive stage in rice - Krishnendu Chattopadhyay; Amaresh Kumar Nayak; Bishnu Charan Marndi; Annie Poonam; Koushik Chakraborty; Ramani Kumar Sarkar (Physiology and Molecular Biology of Plants, 2018)

Isolation and molecular characterization of plant growth-promoting Bacillus spp. and their impact on sugarcane (Saccharum spp. hybrids) growth and tolerance towards drought stress - Priyanka Chandra; Pramila Tripathi; Amaresh Chandra (Acta Physiologiae Plantarum, 2018)

Identification of New Leuconostoc Species Responsible for Post-harvest Sucrose Losses in Sugarcane - Amita Sharma; Amaresh Chandra (Sugar Tech, 2018)

Boron application improves yield of rice cultivars under high temperature stress during vegetative and reproductive stages - Mohammad Shahid; Amaresh Kumar Nayak; Rahul Tripathi; Jawahar Lal Katara; Priyanka Bihari; Banwari Lal; Priyanka Gautam (International Journal of Biometeorology, 2018)

Greenhouse gas emissions and energy exchange in wet and dry season rice: eddy covariance-based approach - Chinmaya Kumar Swain; Amaresh Kumar Nayak; Pratap Bhattacharyya; Dibyendu Chatterjee; Sumanta Chatterjee; Rahul Tripathi; Nihar Ranjan Singh; B. Dhal (Environmental Monitoring and Assessment, 2018)

Measuring potassium fractions is not sufficient to assess the long-term impact of fertilization and manuring on soil’s potassium supplying capacity - Debarup Das; Amaresh Kumar Nayak; V. K. Thilagam; Dibyendu Chatterjee; M. Shahid; Rahul Tripathi; S. Mohanty; Anjani Kumar; B. Lal; Priyanka Gautam; B. B. Panda; S. S. Biswas (Journal of Soils and Sediments, 2018)

Mesoscopic Modeling of Capillarity-Induced Two-Phase Transport in a Microfluidic Porous Structure - Pitambar Randive; Amaresh Dalal; Partha P. Mukherjee (Transport in Porous Media, 2018)

Changes in Growth, Yield, Juice Quality and Biochemical Attributes of Sugarcane in Response to Orthosilicic Acid Granules - Radha Jain; S. P. Singh; Anshu Singh; Smita Singh; Pramila Tripathi; Ram Kishor; Asha Gaur; Neeru Jain; S. K. Shukla; Amaresh Chandra; S. Solomon (Sugar Tech, 2017)

Enhanced biodegradation of low and high-density polyethylene by novel bacterial consortia formulated from plastic-contaminated cow dung under thermophilic conditions - Sinosh Skariyachan; Anagha Shamsundar Setlur; Sujay Yashwant Naik; Ashwini Amaresh Naik; Makam Usharani; Kiran S Vasist (Environmental Science and Pollution Research, 2017)

A new model for estimating End-of-Life disassembly effort during early stages of product design - S. Harivardhini; Amaresh Chakrabarti (Clean Technologies and Environmental Policy, 2016)

Micronutrients (Fe, Mn, Zn and Cu) balance under long-term application of fertilizer and manure in a tropical rice-rice system - Mohammad Shahid; Arvind Kumar Shukla; Pratap Bhattacharyya; Rahul Tripathi; Sangita Mohanty; Anjani Kumar; Banwari Lal; Priyanka Gautam; Rajagounder Raja; Bipin Bihari Panda; Brundaban Das; Amaresh Kumar Nayak (Journal of Soils and Sediments, 2016)

Identification of quantitative trait loci controlling sucrose content based on an enriched genetic linkage map of sugarcane (Saccharum spp. hybrids) cultivar ‘LCP 85-384’ - Pingwu Liu; Amaresh Chandra; Youxiong Que; Ping-Hua Chen; Michael P. Grisham; William H. White; Caleb D. Dalley; Thomas L. Tew; Yong-Bao Pan (Euphytica, 2016)

Loop-mediated isothermal amplification (LAMP) based detection of Colletotrichum falcatum causing red rot in sugarcane - Amaresh Chandra; Amber T. Keizerweerd; Youxiong Que; Michael P. Grisham (Molecular Biology Reports, 2015)

Partial Empty Sella Syndrome: A Case Report and Review - P. Aruna; B. Sowjanya; P. Amaresh Reddy; M. Krishnamma; J. N. Naidu (Indian Journal of Clinical Biochemistry, 2014)

Assessment of genetic diversity and morpho-physiological traits related to drought tolerance in Stylosanthes scabra - Deepti Nagaich; Kapil Kumar Tiwari; Nidhi Srivastva; Amaresh Chandra (Acta Physiologiae Plantarum, 2013)

Physio-Biochemical and Molecular Approaches to Enhance Sucrose Content in Sugarcane: Indian Initiatives - Amaresh Chandra (Sugar Tech, 2011)

Physico-Chemical Method of Preserving Sucrose in Harvested Sugarcane at High Ambient Temperature in a Sub-Tropical Climate - S. Solomon; Priyanka Singh; A. K. Shrivastava; Pushpa Singh; Amaresh Chandra; Radha Jain; C. P. Prajapati (Sugar Tech, 2011)

Screening global Medicago germplasm for weevil (Hypera postica Gyll.) tolerance and estimation of genetic variability using molecular markers - Amaresh Chandra (Euphytica, 2009)

Assessment of ploidy level on stress tolerance of Cenchrus species based on leaf photosynthetic characteristics - Amaresh Chandra; A. Dubey (Acta Physiologiae Plantarum, 2009)

The complete genome sequence of Moorella thermoacetica (f. Clostridium thermoaceticum ) - Elizabeth Pierce; Gary Xie; Ravi D. Barabote; Elizabeth Saunders; Cliff S. Han; John C. Detter; Paul Richardson; Thomas S. Brettin; Amaresh Das; Lars G. Ljungdahl; Stephen W. Ragsdale (Environmental Microbiology, 2008)
Summary This paper describes the genome sequence of Moorella thermoacetica (f. Clostridium thermoaceticum ), which is the model acetogenic bacterium that has been widely used for elucidating the Wood–Ljungdahl pathway of CO and CO 2 fixation. This pathway, which is also known as the reductive acetyl‐CoA pathway, allows acetogenic (often called homoacetogenic) bacteria to convert glucose stoichiometrically into 3 mol of acetate and to grow autotrophically using H 2 and CO as electron donors and CO 2 as an electron acceptor. Methanogenic archaea use this pathway in reverse to grow by converting acetate into methane and CO 2 . Acetogenic bacteria also couple the Wood–Ljungdahl pathway to a variety of other pathways to allow the metabolism of a wide variety of carbon sources and electron donors (sugars, carboxylic acids, alcohols and aromatic compounds) and electron acceptors (CO 2 , nitrate, nitrite, thiosulfate, dimethylsulfoxide and aromatic carboxyl groups). The genome consists of a single circular 2 628 784 bp chromosome encoding 2615 open reading frames (ORFs), which includes 2523 predicted protein‐encoding genes. Of these, 1834 genes (70.13%) have been assigned tentative functions, 665 (25.43%) matched genes of unknown function, and the remaining 24 (0.92%) had no database match. A total of 2384 (91.17%) of the ORFs in the M. thermoacetica genome can be grouped in orthologue clusters. This first genome sequence of an acetogenic bacterium provides important information related to how acetogens engage their extreme metabolic diversity by switching among different carbon substrates and electron donors/acceptors and how they conserve energy by anaerobic respiration. Our genome analysis indicates that the key genetic trait for homoacetogenesis is the core acs gene cluster of the Wood–Ljungdahl pathway.

Plantlet Regeneration via Multiple Shoot Induction in Indian Cultivars of Lucerne (Medicago sativa L) - Suresh Kumar; Amaresh Chandra; Madan G. Gupta (Journal of Plant Biochemistry and Biotechnology, 2008)

Genetical assessment of diploid progenitors of S. scabra by isozyme, RAPD and STS markers: a possible strategy for improvement of drought tolerant allo-tetraploid S. scabra species - Sanchita Tewari; Amaresh Chandra (Euphytica, 2008)

Effect of proteinase inhibitors on Indian alfalfa weevil (Hypera postica Gyll.) growth and development - Amaresh Chandra; Krishna Chandra Pandey (Acta Physiologiae Plantarum, 2008)

Evaluation of genus Cenchrus based on malondialdehyde, proline content, specific leaf area and carbon isotope discrimination for drought tolerance and divergence of species at DNA level - Amaresh Chandra; Archana Dubey (Acta Physiologiae Plantarum, 2007)

Carbon isotope discrimination function analysis and drought tolerance of stylo species grown under rain-fed environment - Amaresh Chandra; R. K. Bhatt (Acta Physiologiae Plantarum, 2007)

Change in phenylalanine ammonia lyase activity and isozyme patterns of polyphenol oxidase and peroxidase by salicylic acid leading to enhance resistance in cowpea against Rhizoctonia solani - Amaresh Chandra; Raghvendra Saxena; Archana Dubey; Pradeep Saxena (Acta Physiologiae Plantarum, 2007)

Electrical Impedance Cardiography Using Artificial Neural Networks - Ajitkumar P. Mulavara; William D. Timmons; Meera S. Nair; Vineet Gupta; Amaresh A. R. Kumar; Bruce C. Taylor (Annals of Biomedical Engineering, 1998)